Pengaruh Economic Value Added, Leverage dan Profitabilitas terhadap Nilai Perusahaan Food dan Beverage - Rido Tua Lumban Tobing; Tri Joko Prasetyo; Rialdi Azhar (Goodwood Publishing, 2022)
This study aims to examine the effect of economic value added, leverageand profitability on firm value. The study was conducted on consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period, the research sample was 38 companies with a total of 190 observations for 5 years. The data analysis method in this study uses path analysis with IBM SPSS 20 software. Based on the results of research that has been carried out, it can be seen that economic value added and profitability have a positive effect on firm value, while the leverage variable has no effect on firm value as measured using Tobin's ratio Q.